Beyond Digital Efficiency: Reconstructing Public Value Through Citizen Satisfaction in Adaptive Governance - Irwan Noor; Hefry Johan Ferdhianza; Dwi Shema Regina; Alya Putri Indrayanti; Shofy Wildan Maulana; Eka Nanda Dwi Aprilia (Spirit Publik: Jurnal Administrasi Publik, 2026)
Digital transformation in public administration is often claimed to generate public value, yet its linking mechanisms remain contested. This study proposes the Public Value Mediation Model in Digital Service Transformation, positioning citizen satisfaction as a transmission mechanism between technological improvements and the formation of perceived public value, as a conceptual contribution to the adaptive governance paradigm, in which adaptivity indicators are operationalized through service responsiveness and flexibility. Departing from Moore's (1995) normative approach, this study operationalizes public value as citizens' subjective assessments of service quality. The study employs an explanatory quantitative design, using a survey of 220 digital service users in Malang City, selected to represent a mid-sized city with measurable digital divides, relevant for testing the limits of digital efficiency claims under uneven infrastructure conditions, with 27 five-point Likert items. The dependent variable is operationalized as a composite public value score. Analysis employs Ordinal Logistic Regression; mediation was tested using the Sobel test, chosen for its suitability with ordinal data, despite its sensitivity limitations compared to bootstrapping. Results show that accessibility (β=0.298, p<0.01) and response speed (β=0.314, p<0.001) significantly enhance satisfaction, which in turn strengthens public value (β=0.382, p<0.001), with 40% partial mediation (Nagelkerke R²=0.642). Critical finding: participation dimensions consistently scored lower than efficiency, indicating a significant efficiency–participation trade-off evidence that digitalization has yet to expand the democratic space of public services. Technological innovation does not automatically generate public value without meaningful citizen experience and attention to the digital divide.